Physical and mental illness comorbidity among individuals with frequent self-harm episodes: A mixed-methods study - Sadath, Anvar; Troya, M. Isabela; Nicholson, Sarah; Cully, Grace; Leahy, Dorothy; Ramos Costa, Ana Paula; Benson, Ruth; Corcoran, Paul; Griffin, Eve; Phillip, Eunice; Cassidy, Eugene; Jeffers, Anne; et al. (Frontiers in Psychiatry, 2023)
Background: Research has indicated an increased risk of self-harm repetition and suicide among individuals with frequent self-harm episodes. Co-occurring physical and mental illness further increases the risk of self-harm and suicide. However, the association between this co-occurrence and frequent self-harm episodes is not well understood. The objectives of the study were a) to examine the sociodemographic and clinical profile of individuals with frequent self-harm (regardless of suicidal intent) episodes and, b) the association between physical and mental illness comorbidity, self-harm repetition, highly lethal self-harm methods and suicide intent. Methods: The study included consecutive patients with five or more self-harm presentations to Emergency Departments across three general hospitals in the Republic of Ireland. The study included file reviews (n=183) and semi-structured interviews (n=36). Multivariate logistic regression models and independent samples t-tests were used to test the association between the sociodemographic and physical and mental disorders comorbidity on highly lethal self-harm methods and suicidal intent respectively. Thematic analysis was applied to identify themes related to physical and mental illness comorbidity and frequent self-harm repetition. Findings: Most participants were female (59.6%), single (56.1%) and unemployed (57.4%). The predominant current self-harm method was drug overdose (60%). Almost 90 % of the participants had history of a mental or behavioural disorder, and 56.8% had recent physical illness. The most common psychiatric diagnoses were alcohol use disorders (51.1%), borderline personality disorder (44.0%), and major depressive disorder (37.8%). Male gender (OR=2.89) and alcohol abuse (OR=2.64) predicted the risk of a highly lethal self-harm method. Suicide intent was significantly higher among those with a diagnosis of major depressive disorder [t=2.43; p=.020]. Major qualitative themes were a) the functional meaning of self-harm b) self-harm comorbidity c) family psychiatric history and d) contacts with mental health services. Participants described experiencing an uncontrollable self-harm urge, and self-harm was referred to as a way to get relief from emotional pain or self-punishment to cope with anger and stressors. Conclusion: Physical and mental illness comorbidity was high among the participants. The comorbidity of individuals with frequent self-harm episodes should be addressed via a biopsychosocial assessment and subsequent indicated treatment interventions.